Technology transfer to the Malaysian telecommunications industry / Abd Aziz Awang - Awang, Abd Aziz (1996)
The aim of this dissertation is to examine the nature of technology transfer in Malaysia with particular reference to the role of multinational corporations in facilitating and hindering technology transfer. The Malaysian telecommunications industry is chosen for this study as a result of increasing attention and dynamic growth of surrounding technology transfer and the practices of multinationals in the industry. It should also be noted that there is a current national and world wide debate concerning the moral and ethical responsibilities of multinationals operating in developing countries, with particular reference to technology transfer and restrictive practices. Since Malaysia has been tagged as a newly industrialising country and telecommunications has been earmarked as the machinery to achieved the developed status, the importance of this study to Malaysia and foreign investors is very obvious. The investigation reveals that both the multinational corporations and the Malaysian government have more to contribute in order to consolidate the mutual benefits of technology transfer accruing to both parties. Having said that, it may well be that the multinational corporations are exploiting the weaknesses of the policies to their utmost benefits jn the satisfaction of their profit maximisation motive. Although some of the issues are dealt with in this dissertation, it should be mentioned that more research should be conducted to accurately determine the extent and ineffective process of technology transfer. It is found that there is still a heavy reliance on FDI and expatriates for the supply of new technology and in the absence of local research and development activity. It is hoped that this study will promote the immediate infrastructure of technology transfer in the telecommunication industry and it is proposed that a pool of local engineers and technologists be created through the establishment of a Telecommunication University to focus on Research and Development as well as continuously providing the expertise on the telecommunications technology. The study should also point the way towards the formulation and implementation of policies for technology transfer in order to achieve the target of developed status by the year 2020.